TBD‐Catalyzed Ring‐Opening Polymerization of Alkyl‐Substituted Morpholine‐2, 5‐Dione Derivatives. Issue 23 (9th August 2018) - Dirauf, Michael; Bandelli, Damiano; Weber, Christine; Görls, Helmar; Gottschaldt, Michael; Schubert, Ulrich S.
Abstract: In a two‐step synthesis, five different alkyl‐substituted morpholine‐2, 5‐dione monomers were synthesized from the natural amino acids glycine, alanine, valine, leucine, and isoleucine. The heterocyclic compounds crystallize in a boat‐like conformation and are polymerized via 1, 5, 7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD)‐catalyzed ring‐opening polymerization (ROP) in tetrahydrofuran. Well‐defined polymers could be obtained from the monomers based on valine, leucine, and isoleucine at a feed ratio of M/I/TBD = 100/1/0.5. Kinetic studies of the ROP reveal that the molar masses and dispersities (Đ < 1.2) could be well controlled, as confirmed by size exclusion chromatography and 1 H NMR spectroscopy. At conversions above 50%, the polymerization rate decreases and the dispersity slightly increases, presumably due to transesterification. Matrix‐assisted laser desorption time‐of‐flight mass spectrometry indicates the presence of polymer chains with α‐end groups derived from the initiator. Abstract : Alkyl‐substituted morpholine‐2, 5‐diones based on the naturall ‐amino acids valine, leucine, and isoleucine are homopolymerized by organobase‐catalyzed ring‐opening polymerization in tetrahydrofuran. Well‐defined polyesteramides with dispersities below 1.2 were obtained until monomer conversions of around 50%, as confirmed by matrix‐assisted laser desorption ionization mass spectrometry, kinetic studies, NMR spectroscopy, and size exclusion chromatography.